MENAKAR PENGARUH PERSONAL SELLING TERHADAP EVALUASI ALTERNATIF KONSUMEN DALAM PEMBELIAN RUMAH SECARA SYARIAH (Riset Di Perumahan Firdaus Garden Paku Haji Kabupaten Bandung Barat) - Ma’mun, Saepul; Solihin, Dadin; Nur Damayanti, Santi (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2021)
Evaluation alternative of the consumer is an activity of selecting two or more product choices with the same type, which requires consumers to consider a product to be purchased before making a decision. Evaluating all product alternatives, consumers will use the information from personal selling. This study aims to determine and analyze the magnitude of the influence of personal selling on the evaluation alternatives of the consumer in buying a house using KPR Syariah at PT. Arkon Multikarya Perdana (Firdaus Garden Pakuhaji in West Bandung Regency). This research is motivated by the problemof the decline in home sales due to weak personal selling strategies carried out by the company due to the presence of covid-19 so that it works with the Work From Home (WFH) system and limits face-to-face sales interactions. The research method used is a combination method or mixed methods with sequential explanatory models. The results of the final conditions of quantitative, the personal selling value are 84.7% and the alternative evaluation value is 84.3% of the ideal condition and qualitatively personal selling and alternative evaluation at PT. Arkon Muktikarya Perdana is good. The results of the research the effect of personal selling on the evaluation alternatives of consumer, with quantitative data the correlation value in the regression results of the number R = 0.599 means that the correlation between variables X and Y is 0.599. R Square is 0.359 or 35.9%, meaning that the percentage contribution of X's influence on Y is 35.9%, while the remaining 64.1% is influenced by other variables outside of this model. The results of the hypothesis t-test, the comparison is t count (6.396) ≥ t table (1.663) and the results of the F test show that F count (5.069) ≥ F table 2.326. This shows that Ha is accepted and Ho is rejected or it can be said that X has a contribution to Y. While the results of qualitative data, personal selling has a role as a bridge for consumers to get clear and detailed information to help consumers evaluate a product with the factors: a) approach; b) presentation; c) overcoming objections; d) close the sale. These factors correlate with the factors that influence the alternative evaluation variable of consumers with the indicators are a) quality of marketing; b) price; c) location; d) promotion. The cumulative results of quantitative data on personal selling variables obtained r count 0.6708 ≥ r table 0.213 and alternative consumer evaluation variables obtained r count 0.6572 ≥ r table 0.213, this shows that the correlation X to Y is included in the strong category. So it can be said that the greater the role of personal selling, the greater will be the evaluation of alternatives made by consumers in buying home products on a Sharia KPR basis. In addition, other variables influence the evaluation alternatives of consumer that are not examined in this study such as consumer finance, trust in property developers, specifications of materials used, house design and facilities provided. So the results of this study can be concluded that there are qualitative data that broadens and deepens quantitative data. Keywords: Personal Selling, Evaluation Alternatives of Consumer.